Poland’s Bilateral Foreign Trade Balances in 1993–2006 - Paweł Młodkowski (Contemporary Economics)
Bilateral trade balances are an important cause for frictions in international trade relations. Therefore, recognizing their causes is essential. The paper presents an attempt to empirically verify theory that could be used for explaining Poland’s foreign trade imbalance. The main hypothesis combines the macroeconomic imbalance with bilateral trade imbalance. The main assumption is that bilateral trade imbalances result from the aggregate trade imbalance. It is somehow natural for countries with permanent deficits in foreign trade to experience bilateral deficits in trade with countries experiencing permanent surpluses. For the studied case of Poland, this theory allows for forecasting trade balances on the basis of aggregate macroeconomic imbalance. Empirical study for the period from 1993 to 2006 shows that there are no reasons to reject the posed hypothesis. However, for forecasting bilateral trade balances the theory is insufficient due to significant asymmetry.